EU counter-terrorism : pre-emption and the rule of law - Murphy, Cian (Cian C.) (Modern studies in European law., 2012)
EU Counter-Terrorism Law: Pre-emption and the Rule of Law is a detailed study of EU action to combat terrorism since 11 September 2001 and the implications that action has had for the EU legal order. It critically examines EU counter-terrorism measures to ascertain how rule of law principles have been affected in the ''war on terror''. The book opens with a critical examination of the rule of law in the EU legal order. It then provides an overview of the war on terror before analysing five key facets of EU counter-terrorism: the common European definition of terrorism along with related off.